2011
DOI: 10.14221/ajte.2011v36n8.1
|View full text |Cite
|
Sign up to set email alerts
|

Democratic Values and Teacher Self-Efficacy Perceptions: A Case of Pre-Service English Language Teachers in Turkey

Abstract: This study investigated democratic values of pre-service English language teachers in relation to their teacher self-efficacy perceptions in a Turkish context. It also examined the possible relationships between gender, grade and democratic values and selfefficacy perceptions. A questionnaire survey was conducted with 294 pre-service teachers. Findings show that they had a high level of democratic values while senior students reported the highest rate of democratic values. Results did not show a significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
(15 reference statements)
3
22
0
3
Order By: Relevance
“…In the findings of the similar studies, even if it was not at a statistically significant level, the girls were seen to be more devoted to democratic values compared to the boys. Thus, it might be stressed that the findings seemed similar to the results obtained from the studies of İlgan et al (2013) and Topkaya and Yavuz (2011). Furthermore, in the study carried out by Yüksel et al (2013), it was restated that being in different cities made significant differences between the students' democratic values.…”
Section: Discussionsupporting
confidence: 84%
“…In the findings of the similar studies, even if it was not at a statistically significant level, the girls were seen to be more devoted to democratic values compared to the boys. Thus, it might be stressed that the findings seemed similar to the results obtained from the studies of İlgan et al (2013) and Topkaya and Yavuz (2011). Furthermore, in the study carried out by Yüksel et al (2013), it was restated that being in different cities made significant differences between the students' democratic values.…”
Section: Discussionsupporting
confidence: 84%
“…The first and most important vertex highlighted in Figure 3 is teacher self-efficacy which appears positively correlated with class management (Silva, Iaochitte, & Azzi, 2010;Abu-Tineh, Khasawneh, & Khalaileh, 2011), motivation (Shaukat & Iqbal, 2012, Kopcha & Alger, 2011Mojavezi & Tamiz, 2012), job satisfaction (Kelm, 2012), democratic values (Topkaya & Yavuz, 2011), autonomy (Skaalvik & Skaalvik, 2010), relationship of the parents, collective efficacy (Kurt, Duyar, & Calik, 2012), relationship between teacher and student (Kim & Kim, 2010), school performance (Corkett, Hatt, & Benevides, 2011;Mojavezi & Tamiz, 2012), desire to remain in the profession (Iaochitte, Azzi, Plydoro, & Winterstein, 2011), inclusion (Tschannen-Moran & Johnson, 2011Malinen et al, 2013); teaching practice (Pan, Chou Hsu, Li, & Hu, 2013;Vieluf, Kunter, & Vijver, 2013); school's organizational structure (Hemric, Eury, & Shellman, 2010).…”
Section: Relations Among the Variables Identified In The Studies On Tmentioning
confidence: 99%
“…Democratic values and attitudes of teachers have an impact on teachers' decisions and practices (Topkaya and Yavu, 2011). In a study, Topkaya and Yavu (2011) investigated democratic values and teacher self-efficacy perceptions of 294 pre-service English teachers in the Turkish context.…”
Section: Kaya 2105mentioning
confidence: 99%
“…In a study, Topkaya and Yavu (2011) investigated democratic values and teacher self-efficacy perceptions of 294 pre-service English teachers in the Turkish context. Results indicated that they gained very high democratic values but there was no significant differences based on gender.…”
Section: Kaya 2105mentioning
confidence: 99%